The Postcolonial State in Africa : Fifty Years of Independence, 1960-2010 - Young, Crawford, 1931- (Book collections on Project MUSE., 2012)
"An interesting, thoughtful, and comprehensive work rich in case material and analysis; the incorporation of the analysis of the North African states is particularly noteworthy. The scope of Young's knowledge and mastery of the scholarly literature is truly impressive."--Catherine Boone, author of Political Topographies of the African State: Territorial Authority and Institutional Choice --Book Jacket.